58. Central motor conduction time along the phrenic nerve pathway and fiber tracking in Chiari and Syringomyelia. Issue 12 (December 2016) - Ciaramitaro, P.; Ferraris, M.; Spagone, E.; Giorgi, S.; Peci, E.; Audisio, A.; Curreri, L.; Robella, M.; Valentini, M.C.; Cocito, d.
Abstract : Cortico-diaphragmatic pathway was investigated with transcranial magnetic stimulation (TMS) in amyotrophic lateral sclerosis without clinical signs of respiratory impairment revealing subclinical diaphragmatic impairment. Diffusion Tensor Imaging with fiber tracking (DTI-FT) through fractional anisotropy (FA) measurement was tested for the assessment of spinal sensory tract lesions in cervical syringomyelia (Syr). The aims of this work was to investigate: (1) central motor conduction time (CMCT) in Syr and Chiari Malformation (CM) to point out subclinical alterations of phrenic pathway; (2) relationship between CMCT and structural damage in Syr/CM through FA. 100 patients (75F, 18–76 years, 51 ± 13.08 years) were selected. Latency/amplitude of cortical/spinal motor-evoked potentials (Cx/Sp-MEP) and CMCT along phrenic nerve were measured and compared with healthy subjects. FA measurement was carried out in 13 patients and compared with neurophysiological data. CMCT was significantly altered ( p  < 0, 05) in: Syr with CM, Syr with CM and surgery. T-student analysis on FA between patients with altered and normal CMCT showed a significant difference ( p  < 0, 05). The reduced values of Sp-MEP may be related to the fibers loss along the cortical-spinal way and to primitive axonal damage of spinal motoneurons linked to diaphragmatic muscle. CMCT and FA alterations might have a prognostic relevance in the clinical monitoring of these patients.